PROBLEMATIK PENUGASAN GURU SEBAGAI KEPALA SEKOLAH NEGERI DI KOTA PEKANBARU TAHUN 2013-2014 - Pakpahan, Fernandes; Ridwan, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to investigate the implementation of the nationaleducation ministerial regulation number 28 of 2010 on assignment teacher asprincipal of a public school in the city of Pekanbaru in 2013-2014 and efforts arebeing made to overcome the problems in the implementation of the nationaleducation ministerial regulation No. 28 of 2010 is.This study uses the theory of policy implementation by Van Meter andVan Horn who says there are six variables that affect the performance ofimplementation, namely: standards and policy goals, resources, communicationamong organizations, characteristic of the implementing agencies, environmental /social conditions, economic and political as well as the disposition of theimplementor.This research is a descriptive study using a qualitative approach. Thesampling technique used is purposive sampling. The informants in this study areHead of Education Department Pekanbaru, Head of Kindergarten and ElementaryEducation Department Pekanbaru, Head of Staffing Agency Pekanbaru,Pekanbaru City Council Member, Member of Pekanbaru City Board of Education,Coordinator of School Supervisors, Education Leaders Pekanbaru and PrincipalParticipants. The technique of collecting data uses interviews and documentation.Types and sources of data are primary and secondary. Data were analyzed usinginductive analysis techniques.Based on the results of this study concluded that the implementation of thenational education ministerial regulation policy on assignment of teacher asprincipal have not been implemented properly because of communication isestablished between the implementing organization is not good, limited humanresources, yet the realization of education and training candidates for theprincipal. As an attempt to overcome problems in implementing nationaleducation ministerial regulation include: policy socialization of the nationaleducation ministerial regulation number 28 of 2010 to teachers and principals,principal restraints which have exceeded the period of the task, theimplementation of recruiting candidates for the principal and improved standardsof school leadership.Keywords: Policy, policy implementation, assignment teacher as principal,principal